2019
DOI: 10.1016/j.jsxm.2019.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Are There Differences in Brain Morphology in Patients with Lifelong Premature Ejaculation?

Abstract: Introduction Even though lifelong premature ejaculation (PE) is highly prevalent, few studies have investigated the neural mechanisms underlying PE. Aim This study aimed to investigate whether patients with lifelong PE exhibit macrostructural or microstructural alterations of the parts of the brain involved in the male sexual response. Materials and Methods W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 25 publications
0
20
3
Order By: Relevance
“…The phase of expulsion is controlled by the parasympathetic and somatic nervous system, as well as the perineal muscles (Alwaal et al, 2015;Clement & Giuliano, 2016;Ch ehensse et al, 2017a,b). The events of peripheral neural system are under the control of spinal centers including the spinal generator of ejaculation (SGE) (Chehensse et al, 2016;Ch ehensse et al, 2017a,b;de Rodr ıguez-Peña et al, 2017), which is regulated by the excitatory and inhibitory inputs from the brain (Qin et al, 2017;Zhang et al, 2017;Atalay et al, 2019;Xu et al, 2019). Therefore, the brain is also responsible for these two phases and it is especially involved in the pleasant sensation produced by the orgasm reaction (Flannigan et al, 2018;Wise et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The phase of expulsion is controlled by the parasympathetic and somatic nervous system, as well as the perineal muscles (Alwaal et al, 2015;Clement & Giuliano, 2016;Ch ehensse et al, 2017a,b). The events of peripheral neural system are under the control of spinal centers including the spinal generator of ejaculation (SGE) (Chehensse et al, 2016;Ch ehensse et al, 2017a,b;de Rodr ıguez-Peña et al, 2017), which is regulated by the excitatory and inhibitory inputs from the brain (Qin et al, 2017;Zhang et al, 2017;Atalay et al, 2019;Xu et al, 2019). Therefore, the brain is also responsible for these two phases and it is especially involved in the pleasant sensation produced by the orgasm reaction (Flannigan et al, 2018;Wise et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Increased aromatase activity secondary to the accumulation of adipose tissue may be a plausible explanation because of the significant positive correlation between BMI and E2 in our patients. However, secondary PE showed significantly higher BMI compared to primary PE and the control group that could be explained by the fact that primary PE has been viewed as a neurobiological defect rather than a hormonal dysfunction (34) ; nevertheless; the condition appears to be more complex and may include other significant biological components (35) .…”
Section: Discussionmentioning
confidence: 94%
“…In this study, both the degree and betweenness centrality of ORBmid.R were abnormal in the group of PE with depression when compared with the groups of HC and PE without depression. The prefrontal cortex, especially the orbitofrontal cortex was supposed to play an important role in the occurrence, maintenance, remission of depressive symptom (Frodl et al., 2010; Scheuerecker et al., 2010) and was also considered to be involved in the aetiology of PE (Atalay et al., 2019; Guo et al., 2018). Previous studies had demonstrated that the orbitofrontal cortex, a part of prefrontal cortex was involved in the regulation of cognition, emotion and attention (Rolls & Grabenhorst, 2008; Golkar et al., 2012), as well as the inhibitory control over sexual activity (Cheng et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PE is not only a common symptom of depression but also a frequent side‐effect of the selective serotonin reuptake‐inhibitors (SSRIs), which is a first line treatment option of antidepressant medication (Castiglione et al., (2016); Chokka & Hankey, 2018). Therefore, PE is considered as a complex interaction of psychological and biological factors, including depression and abnormal function and structure of certain brain areas (Zhang et al., 2017; Atalay et al., 2019).…”
Section: Introductionmentioning
confidence: 99%